ANALISIS PERAN BIROKRASI DALAM IMPLEMENTASI KEBIJAKAN PUBLIK DI ERA DIGITAL - Wahyuni, Made Dewi; Sudiari, Made; Murdiati, Ni Ketut; Kapu, Maria Oktaviani (Universitas Mahendradatta Denpasar, 2025)
The digital era has brought significant changes in government governance, including the implementation of public policies. The bureaucracy, as one of the main actors in this process, faces the challenge of adapting to developments in information and communication technology (ICT) in order to increase efficiency, transparency and accountability. This research aims to analyze the role of bureaucracy in implementing public policy in the digital era, with a focus on the use of digital technology to support administrative processes and decision making. The approach used is a qualitative method with data collection through in-depth interviews, document studies and participant observation. This research also explores factors that influence the effectiveness of bureaucracy in adopting digital innovation, such as human resource capacity, technological infrastructure support, and supportive regulations. It is hoped that the research results can provide theoretical and practical contributions in understanding the dynamics of bureaucracy in the midst of digital transformation, as well as provide recommendations for developing policies that are adaptive and responsive to community needs. Thus, this research can be a stepping stone in encouraging a bureaucracy that is more professional and oriented towards technology-based public services in the future.